(untitled) (International Journal of Physiology, 2019)
Introduction In today’s multifaceted & challenging context of medical education, students are unable to organise, integrate information to the medical problems, so a need to fill this gap is strongly felt. The purpose of this study was to evaluate the effectiveness of Concept Mapping (CM) over the traditional method of teaching & learning. Aims & Objectives To compare learning by traditional lecture with lecture using CM. To foster meaningful learning using CM & boosting the relevance of topic. To obtain feedback & reflection for CM based learning. Materials & Method Total 112 students were taken for the study. They were divided randomly in two groups. For group-A, lecture on Systemic lupus erythematous was taken by traditional method of teaching. For group-B lecture was taken by using concept mapping of same topic. Post-test (10 Marks MCQs) was taken from both groups & comparing was done. Cross over study was conducted for ethical purpose. Reflection & feedback was taken from students about CM. Result The result of post-test shows significant (P<0.01) rise in marks in Group B (CM) as compare to Group A (Traditional method), suggesting CM as a potential tool for better understanding & easy recall. Regarding reflection of students about concept method over traditional lecture method it was observed that more than 90% students said that it is simpler, easy, smart, concise, efficient and effective method of learning. Conclusion Students found it very interesting & effective tool for learning. Students also feel that this method will be helpful for revision before the sessional & professional examination.